2014
DOI: 10.1007/s00572-014-0559-6
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Tuber melanosporum extramatrical mycelium expansion over a 20-year chronosequence in Quercus ilex-truffle orchards

Abstract: Successful cultivation of black truffle (Tuber melanosporum) requires a long-term investment and the maintenance of the symbiosis throughout its preproductive and productive years. Monitoring the symbiosis over time is challenging, as it requires methods that can detect the belowground proliferation of the fungus associated with its host tree. In this study, we used a chronosequence design to study the expansion pattern of this fungus as the host tree grows. We hypothesize that this expansion can be estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…belonging to T. melanosporum and, with a fluctuation in the 10-year-old plantation, continued to increase through the 20-year plantation with 22 of 31 (71% of colonies) belonging to T. melanosporum, confirming its dominating capacity. This domination was also reflected in the relative quantities of T. melanosporum mycelium detected in soils from these plantations in a companion work by Liu et al (2014).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…belonging to T. melanosporum and, with a fluctuation in the 10-year-old plantation, continued to increase through the 20-year plantation with 22 of 31 (71% of colonies) belonging to T. melanosporum, confirming its dominating capacity. This domination was also reflected in the relative quantities of T. melanosporum mycelium detected in soils from these plantations in a companion work by Liu et al (2014).…”
Section: Discussionmentioning
confidence: 81%
“…in collaboration with truffle farmers who have established successful black truffle plantations in the province of Teruel, (central eastern Spain). As reported in Liu et al (2014): Plantations are located in the valley between the ranges of Gudar and Javalambre, on relatively homogeneous calcareous soils with Tertiary sediments. The latitudes of the plots range from N 40º 20' to N 40º 2' and the longitudes from W 1º 10' to W 0º 41', with altitudes from 843 to 1124 m a.s.l.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The methods for quantifying mycelium of T. melanosporum in the soil have allowed Liu et al (2014) to monitor its spread and increase of density in young plantations. Suz et al (2008) showed the relation between the abundance of mycelium and the formation of the brûlé.…”
Section: Basic Researchmentioning
confidence: 99%
“…Sánchez et al (2014) present an easy and reliable method to quickly check for the presence of T. melanosporum ectomycorrhiza on Q. ilex plantation trees and conclude that only three trees need sampling to provide a reasonable estimate of black truffle ectomycorrhiza presence. Liu et al (2014) examine the rate of black truffle mycelial spread on Q. ilex plantation trees of different ages and report that mycelium extension reaches a maximum from the base of trees after 7 to 10 years. These findings address important questions regarding tree density in plantations and the potential for different dominant truffle mating types on individual trees to contact one another and initiate sporocarp formation.…”
Section: Purpose and Content Of This Special Issuementioning
confidence: 99%